Vermicompost quality of oyster mushroom Baglogs waste and pineapple residue mix - Lia Hadiawati; Ahmad Suriadi; Syarifinnur Syarifinnur; Khaerana Khaerana; Yudhistira Nugraha; Zaenal Arifin; Lolita Endang Susilowati (International Journal of Recycling of Organic Waste in Agriculture)
Purpose: The study aimed to examine the quality of vermicompost produced through the combination of oyster mushroom Baglogs and pineapple waste using the Eudrillus eugeniae species as a decomposer.